The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4322/polimeros.2013.081
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de Plastificantes à base de Poliisobutenos nas Propriedades Físicas e Mecânicas do Polipropilen

Abstract: IntroduçãoO polipropileno (PP) é um dos polímeros termoplásticos mais utilizados pela indústria, com uma diversidade de aplicações que incluem embalagens rígidas e flexíveis, descartáveis, tubos e produtos injetados para os mais variados usos. A indústria petroquímica disponibiliza vários tipos de polipropilenos, quais sejam: PP homopolímero, PP copolímero heterofásico e PP copolímero randômico. O PP homopolímero contém apenas o monômero propeno em sua cadeia molecular e, sendo predominantemente de configuraçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…As for the composites with oil, there was a significant reduction in the degree of crystallinity, probably because the oil hindered the formation of crystals, hindering molecular packing and reducing crystallinity. [60] The composites showed three decomposition stages: the first occurs in the room temperature range up to 100 C, attributed to water loss by desorption [61] ; the second loss occurs after 200 C attributed to the decomposition of the MS and oil components [62] ; the third mass loss event was attributed to the decomposition of the BioPE chain and at the same time cellulose, hemicelluloses and lignin.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…As for the composites with oil, there was a significant reduction in the degree of crystallinity, probably because the oil hindered the formation of crystals, hindering molecular packing and reducing crystallinity. [60] The composites showed three decomposition stages: the first occurs in the room temperature range up to 100 C, attributed to water loss by desorption [61] ; the second loss occurs after 200 C attributed to the decomposition of the MS and oil components [62] ; the third mass loss event was attributed to the decomposition of the BioPE chain and at the same time cellulose, hemicelluloses and lignin.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…The collected data show a clear reduction of T d10% in the addition of MS, this behavior may be related to the fact that MS is a natural filler. [63] The MO addition to BioPE brought the weight loss (T d50% ) to a higher temperature, around 458 C. According to the literature, [60] the use of natural oil in composites can improve thermal stability, thus MO acted as a plasticizing agent and with good thermal stability. The BioPE/PE-g-MA/MS and BioPE/PE-g-AA/MS composites improved T d10% relative to the BioPE/MS composites, suggesting good interaction between the phases.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Regarding the MA degree of grafting, increasing from 0.73% to 2.1% in the PCL-g-MA compatibilizer had little effect on T m , as seen in Table 5. As T m reduction is often associated with the degree of crystal perfection, 45 it is suggested that the PCL/ JWF and PCL/JWF/PCL-g-MA biocomposites presented less perfect and/or smaller crystals in relation to PCL. Similar behavior was reported by Machado et al 46 with polyhydroxybutyrate (PHB)/wood powder composites, indicating that the wood powder in the thermoplastic matrix hinders the crystals formation, therefore non-uniform thickness crystals are formed, decreasing T m .…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…The melting temperature of the PLAr was around 172.9 °C, lower when compared to Research, Society and Development, v. 9, n. 12, e13291210767, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.10767 the PLA's. As the reduction in the melting temperature is often associated with the crystal's degree of perfection (Nascimento et al, 2013), it is suggested that the lower molar mass of the PLAr has nucleated smaller and less thick crystals, reducing its degree of perfection.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%